Ответ:
K2S + NiSO4 → K2SO4 + NiS↓
полное ионное ур-е: 2K(+) + S(2-) + Ni(2+) + SO4(2-) = 2K(+) + SO4(2-) + NiS↓
сокращенное ионное ур-е: S(2-) + Ni(2+) = NiS↓
Fe2(SO4)3 + 6KOH → 3K2SO4 + 2Fe(OH)3↓
полное ионное ур-е: 2Fe(3+) + 3SO4(2-) + 6K(+) + 6OH(-) = 6K(+) + 3SO4(2-) + 2Fe(OH)3↓
сокращенное ионное ур-е: 2Fe(3+) + 6OH(-) = 2Fe(OH)3↓
Ca(NO3)2 + K2CO3 → 2KNO3 + CaCO3↓
полное ионное ур-е: Ca(2+) + 2NO3(-) + 2K(+) + CO3(2-) = 2K(+) + 2NO3(-) + CaCO3↓
сокращенное ионное ур-е: Ca(2+) + CO3(2-) = CaCO3↓
H2SO4 + 2RbOH → Rb2SO4 + 2H2O
полное ионное ур-е: 2H(+) + SO4(2-) + 2Rb(+) + 2OH(-) = 2Rb(+) + SO4(2-) + 2H2O
сокращенное ионное ур-е: 2H(+) + 2OH(-) = 2H2O